Recasamento: percepções e vivências dos filhos do primeiro casamento - Amaral, Daniela Heitzmann (2010)
Remarriage is occurring with great frequency, mainly due to the number of separations and divorces. Adaptation between the several members, in this new family, can bring them a lot of suffering, due the need of knowledge, time and flexibility that such configuration demands. The children, especially, can suffer loneliness, abandonment, identity and loyalty conflicts, among others, and develop symptoms and difficulties that need to be understood and faced. The present research has investigated how children understood and experienced the changes that occurred in their lives in due to remarriage of one or both parents. It is a qualitative research attended by four adolescents and young adults, aged between 15 and 24 years, single, middle-class, who have answered a semi-directed interview, composed of questions referring to the study goals and socio-demographic data of the participants. The answers to the interview were analyzed based on the following themes: parent relationship before and after remarriage; living experience with the stepparent; organization of the fraternal subsystem; fraternal relationship peculiarities; new family, new rules; children expectations in the remarried family. It can be concluded that, besides initial troubles due to changes in the physical structure (loss of privacy), routine (new habits and rules), and house dynamics, with introduction of new characters (stepparent, stepbrothers and political or convivial brothers), the participants referred more positive than negative aspects in this configuration, except in one case that presents troubles in interaction and living with the stepmother. It is expected to contribute in a way to broaden the understanding and visibility of this family configuration, as well as provide subsidies for the work of professionals that deal with families, adolescents and young adults, since research related to this subject is scarce in the northeastern reality.